Understanding of Solid-Fluid Kinetics and Mass Transfer: From Ideal to Non-ideal Models, From Perfect Spheres to Moon Landscape - Salmi, Tapio; Wärnå, Johan; Tolvanen, Pasi (Frontiers in Chemical Engineering, 2020)
Throughout the decades, the solid-fluid processes have been modelled with the hypothesis of ideal, non-porous particles. Numerous relevant industrial reactions with reactive solids do not involve ideal slabs, spheres or cylinders, but instead the particles have rough surfaces comparable of the Moon with cracks and craters. The theory of non-ideal solid particles is briefly reviewed and the effect of the non-ideality is illustrated for batch processes. In general, surface roughness results in the increase of the apparent reaction with respect to the solid reactant.